Asymmetric Electron Acceptors for High‐Efficiency and Low‐Energy‐Loss Organic Photovoltaics. Issue 24 (11th May 2020) - Li, Shuixing; Zhan, Lingling; Jin, Yingzhi; Zhou, Guanqing; Lau, Tsz‐Ki; Qin, Ran; Shi, Minmin; Li, Chang‐Zhi; Zhu, Haiming; Lu, Xinhui; Zhang, Fengling; Chen, Hongzheng
Abstract: Low energy loss and efficient charge separation under small driving forces are the prerequisites for realizing high power conversion efficiency (PCE) in organic photovoltaics (OPVs). Here, a new molecular design of nonfullerene acceptors (NFAs) is proposed to address above two issues simultaneously by introducing asymmetric terminals. Two NFAs, BTP‐S1 and BTP‐S2, are constructed by introducing halogenated indandione (A1 ) and 3‐dicyanomethylene‐1‐indanone (A2 ) as two different conjugated terminals on the central fused core (D), wherein they share the same backbone as well‐known NFA Y6, but at different terminals. Such asymmetric NFAs with A1 ‐D‐A2 structure exhibit superior photovoltaic properties when blended with polymer donor PM6. Energy loss analysis reveals that asymmetric molecule BTP‐S2 with six chlorine atoms attached at the terminals enables the corresponding devices to give an outstanding electroluminescence quantum efficiency of 2.3 × 10 −2 %, one order of magnitude higher than devices based on symmetric Y6 (4.4 × 10 −3 %), thus significantly lowering the nonradiative loss and energy loss of the corresponding devices. Besides, asymmetric BTP‐S1 and BTP‐S2 with multiple halogen atoms at the terminals exhibit fast hole transfer to the donor PM6. As a result, OPVs based on the PM6:BTP‐S2 blend realize a PCE of 16.37%, higher than that (15.79%) of PM6:Y6‐based OPVs. A further optimization of the ternary blend (PM6:Y6:BTP‐S2) results in a best PCE of 17.43%, which is among the highest efficiencies for single‐junction OPVs. This work provides an effective approach to simultaneously lower the energy loss and promote the charge separation of OPVs by molecular design strategy. Abstract : Asymmetric electron acceptors, by combining halogenated indandione and 3‐dicyanomethylene‐1‐indanone as two different conjugated terminals, are designed and synthesized. Such design enables reduced energy loss and boosts charge separation, thus leading to 16.37% binary organic photovoltaics (OPVs) and 17.43% ternary OPVs, which are among the best efficiencies for single‐junction OPVs.